2019
DOI: 10.1016/j.heares.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The power of language: Functional brain network topology of deaf and hearing in relation to sign language experience

Abstract: Prolonged auditory sensory deprivation leads to brain reorganization, indicated by functional enhancement in remaining sensory systems, a phenomenon known as cross-modal plasticity.In this study we investigated differences in functional brain network shifts from eyes-closed to eyes-open conditions between deaf and hearing people. Electroencephalography activity was recorded in deaf (N = 71) and hearing people (N = 122) living in rural Africa, which yielded a unique data-set of congenital, pre-lingual and post-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 138 publications
(136 reference statements)
1
14
2
Order By: Relevance
“…There is also a stronger functional connectivity between sensory processing cortices in adults with long-term sensory deprivation compared to normal individuals. For example, human studies revealed a stronger functional connectivity between the auditory, visual, and/or somatosensory in early deaf [electroencephalography: Sinke et al, 2019; functional magnetic resonance imaging (fMRI): Shiell et al, 2015; Bola et al, 2017] and blind people (resting-state fMRI: Pelland et al, 2017; dynamic causal modeling (DCM) of fMRI data: Collignon et al, 2013) and between V1 and S1 in Braille reading blinds (rsfMRI: Liu et al, 2007; DCM: Fujii et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a stronger functional connectivity between sensory processing cortices in adults with long-term sensory deprivation compared to normal individuals. For example, human studies revealed a stronger functional connectivity between the auditory, visual, and/or somatosensory in early deaf [electroencephalography: Sinke et al, 2019; functional magnetic resonance imaging (fMRI): Shiell et al, 2015; Bola et al, 2017] and blind people (resting-state fMRI: Pelland et al, 2017; dynamic causal modeling (DCM) of fMRI data: Collignon et al, 2013) and between V1 and S1 in Braille reading blinds (rsfMRI: Liu et al, 2007; DCM: Fujii et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby it minimizes the sum of the costs of all edges over the set of all possible MSTs that could be constructed from the original graph (Hidalgo et al, 2007). The usefulness of MST analysis has been shown in previous studies on ageing (Boersma et al, 2013;Otte et al, 2015;Smit et al, 2016), multiple sclerosis (Engels et al, 2015;Tewarie et al, 2015b), epilepsy (van Diessen et al, 2016, which we extended with our studies on deafness (Sinke et al, 2019) and stroke (chapter 4). MSTs seem to able to capture similar network characteristics as classical graph analysis, without being biased by the number of nodes and edges (Tewarie et al, 2015a;van Wijk et al, 2010).…”
Section: Brain Network Analysis Methodssupporting
confidence: 52%
“…Once this step of artifact rejection had been completed, we then interpolated the rejected electrodes. Furthermore, previous studies have found that using multiple epochs per subject increases the stability of network metrics ( 43 , 61 ). Therefore, to ensure the stability of the results and to exclude the possible influence of the number of epochs per subject on the results, the number of epochs in the present study was set to 72 for all subjects in both the EC and EO conditions.…”
Section: Discussionmentioning
confidence: 98%
“…There is accumulating evidence that MST analysis can capture subtle changes in brain networks during human development ( 59 , 60 ), and this approach has been used extensively in EEG resting-state data from diverse populations, including people with deafness ( 61 ), autism ( 62 ), Alzheimer's disease ( 63 ), and dyslexia ( 46 ). In a recent EEG resting-state study, MST analysis was used to compare brain network characteristics between deaf and hearing controls in different resting states ( 61 ). The results showed differences in the topological characteristics of brain networks between the deaf group and the hearing group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation